KORELASI BIMBINGAN PRAKTIK KERJA INDUSTRI DAN PRESTASI PRAKTIK KERJA INDUSTRI DENGAN MINAT BEKERJA PADA SISWA KELAS XII BIDANG KEAHLIAN TEKTIK MEKANIK OTOMOTIF SMK TAMANSISWA JETIS YOGYAKARTA TAHUN AJARAN 2013/2014 - Lulut Setiya Priyanto; Slamet Priyanto (Jurnal Taman Vokasi, 2014)
This study aimed to determine: (1) correlation with the guidance of industry working practices working interest in class XII Automotive Engineering Expertise. (2) the correlation of achievement with industry work practices working interest in class XII Automotive Engineering Expertise. (3) correlation guidance of industry working practices and achievements of the industry work practices with an interest to work in class XII Automotive Engineering Expertise SMK Yogyakarta Tamansiswa Jetis Academic Year 2013/2014.This research is ex post facto research, data collection techniques using questionnaires and documentation. The population in this study were students of class XII Automotive Engineering Expertise at the SMK Yogyakarta Tamansiswa Jetis totaling 82 respondents as well as a sample in this study. Prior to the study, the instrument first tested on 29 students of class XII SMK Piri 1 Yogyakarta. Having piloted tested the validity and reliability to determine the item valid and reliable instrument. Engineering data analysts used in this study is hypothesis testing, prior to testing the hypothesis, first tested as a condition of a requirements analysis so that the analysis of the research actually has a high reliability. Test requirements analysis done by testing normality, linearity test and test intercorrelations. After test requirements are met analysis tested the hypothesis. Test this hypothesis using multiple regression and partial correlation. The results showed that: 1) the guidance of industry working practices (X1) and the achievements of the industry work practices (X2) are jointly positively correlated with interest in working on the student (Y) class XII Expertise Automotive Engineering, 2) industry practice guidance ( X1) partially positively correlated with interest in working on the student (Y) class XII Expertise Automotive Engineering, 3) achievement of industry working practices (X2 ) partially positively correlated with interest in working on the student (Y) class XII Mechanical Engineering Expertise automotive.